Ning Qing 3: A New Holly Cultivar with Peculiar Leaf Morphology - Xinran Chong; Xiaolong Wang; Bingsong Zheng; Ting Zhou; Yunlong Li; Chuanyong Wang; Fan Zhang; Yanwei Zhou; Hong Chen (HortScience, 2023)
The Ilex L. (holly) is the largest woody dioecious angiosperm genus in Aquifoliaceae, composed of ∼700 deciduous and evergreen trees and shrubs (Chong et al. 2022; Manen et al. 2010; Yao et al. 2022). The genus is distributed worldwide from tropical to temperate regions, with centers of species diversity located in East Asia and South America (Su et al. 2020; Yao et al. 2016). For tens of decades, Ilex species have been used as ornamentals, beverages, pharmaceutical plants, and industrial materials (Li et al. 2022; Yao et al. 2022; Zhou et al. 2022). The flowers and fruits of holly are fairly uniform, but leaf characters vary greatly among species in this genus, including size, shape, margins, and texture. Many Ilex species are widely cultivated as ornamental plants because of their red drupes and often distinctive leaves. Therefore, many breeders and consumers pay much attention to the leaf traits of Ilex plants.